Range extension and description of the juvenile plumage of the Masked Mountain-tanager (Buthraupis wetmorei, Thraupidae) - Leal, César (2011)
Here we report the first record of the Masked Mountain-Tanager (Buthraupis wetmorei) for the Eastern Andes of Colombia, which represents the discovery of the most northern and isolated population (c. 450 km from the nearest locality) of this rare species. The Masked Mountain-Tanager inhabits locally the ecotone between humid elfin Andean forests and paramo. Up to now, it was known from scattered localities from the Huancabamba region in northernmost Peru to the middle section of the Central Andes in Quindío, Colombia. We report observations and photographs of this species from the Tamá National Park, Norte de Santander, Colombia. We found various adults and juveniles joining a flock with the Golden-crowned Tanager (Iridosornis rufivertex) at 3050 m elevation in a subparamo/treeline transition zone. Based on photographs from Tamá and a specimen from Tungurahua, Ecuador, we comment on the juvenile plumage of the Masked Mountain-tanager.